The influence of type of vascular pedicle occlusion on the viability of skin island flaps: a postoperative quantitative assessment of flap survival in an experimental model in rats - Gemperli,Rolf (2013)
PURPOSE: To evaluate the role of pedicle occlusion on the viable area of a skin island flap. METHODS: An epigastric skin island flap was performed in 160 Wistar rats. The animals were randomly divided into four groups: G-1: occlusion of inferior epigastric artery; G-2: inferior epigastric vein; G-3: inferior epigastric vessels (artery/vein). At varying times postoperatively (2,3,4,5th day), animals from each group were randomly selected, and the pedicle was occluded. On the 10th. postop. day, the skin flaps were evaluated by templates to determine the percentage of surviving skin. The computer HP™ 9830A captured the photographs and the mean flap necrosis area was assessed. RESULTS: An increasing area of flap survived with less area of necrosis with increased time of days intervals. In the G-1, the mean area of necrosis observed (two to five days) were 95.2, 60.8, 31 and 3.7 % respectively. In the G-2 were 95.5, 57.6, 19.5 and 5.6 % respectively. In the G-3, a 100, 80, 32.4 and 14.9 % of mean area was observed. CONCLUSIONS: The arterial suppy/venous drainage is important for flap circulation up to five days following pedicle occlusion. After this period, the pedicle can be interrupted once the circulation through the flap margins has already been established.